Maltotriose Conjugated Metal–Organic Frameworks for Selective Targeting and Photodynamic Therapy of Triple Negative Breast Cancer Cells and Tumor Associated Macrophages. Issue 8 (8th June 2020) - Sakamaki, Yoshie; Ozdemir, John; Diaz Perez, Alda; Heidrick, Zachary; Watson, Olivia; Tsuji, Miu; Salmon, Christopher; Batta‐Mpouma, Joseph; Azzun, Anthony; Lomonte, Valerie; Du, Yuchun; Stenken, Julie; et al.
Abstract: Metal–organic frameworks (MOFs) are a well‐suited platform for drug delivery systems that can affect photodynamic therapy (PDT). A well‐designed PDT delivery system to treat cancer can overcome some problems of current PDT such as prolonged photosensitivity and tumor specificity. Triple negative breast cancer (TNBC) is difficult to treat with existing chemotherapy and often requires surgery because it quickly metastasizes throughout the body. Tumor associated macrophages (TAM) are known to be M2‐like macrophages, which are involved in processes of cancer progression, such as angiogenesis, matrix remodeling, and metastases. These roles are brought on by the expression of the CD206 (mannose receptor) on the surface of the macrophage. MOF nanoparticles around 50 nm are synthesized by a solvothermal reaction of Mn(III)‐tetrakis(4‐carboxyphenyl) porphyrin, tetrakis(4‐carboxyphenyl) porphyrin, and ZrOCl2 . Through postsynthetic modification, Zn(II) is incorporated into the tetrakis(4‐carboxyphenyl) porphyrin sites and potassium maltotrionate is conjugated with the empty coordination sites on the Zr6 O4 (OH)4 clusters. The resultant maltotriose‐PCN‐224‐0.1Mn/0.9Zn is able to specifically target tumor cells and TAM. Upon irradiation by a light‐emitting diode (LED) source, TNBC and the TAM cells were selectively targeted by MA‐PCN‐224‐0.1Mn/0.9Zn via the glucose transporter (GLUT) and CD206 receptors. The MA‐PCN‐224‐0.1Mn/0.9Zn shows no toxicity toward normal cell lines and no dark toxicity. Abstract : Metal–organic framework (MOFs) nanoparticles conjugated to maltotriose are reported as a new drug delivery system (DDS). The MOF; MA‐PCN‐224‐0.1Mn/0.9Zn (PCN = porous coordination network), is a photosensitizer (PS) which is able to target cancer cells and tumor‐associated macrophages (TAM). PCN‐224‐0.1Mn/0.9Zn can affect photodynamic therapy (PDT) upon irradiation with a light‐emitting diode (LED) source. An effective size‐control methodology for PCN‐224 nanoparticles is also described.